Assessment of bag net fishery of Narmada estuary, Gujarat: A case study - Bhakta, Dibakar; Meetei, W Anand; Solanki, J K; Manna, R K; Das, S K; Das, B K (Journal of the Inland Fisheries Society of India, 2021)
Bag net, locally known as â€˜Golava,â€™ is an important means of fishing in the middle stretch of Narmada estuary for the livelihood security of many stakeholders. The present study was conducted during 2015-16 to find out species composition and economic evaluation of bag net fishery in the Narmada estuarine region. Bag net was operated for 7-8 months with peak duirng November to February. A total of 7-8 sets of bag nets were found to be operated from Bhadhut (21o 41’ 108" N, 72o 51â€™ 198" E) to Mehgam (21o 40’ 44" N, 72o 45â€™ 27" E) region. In a single set, a total of 12-22 numbers of bag nets were installed with an average individual net length of 25-27 m with 10 mm cod-end mesh size. The nets were installed in the current-driven area during low as well as high tides to harvest fishes during high tides and low tides, respectively. A total of 8-12 fishers were involved in the total installation. The operational time of the bag net is around 10-12 hours. The mean catch per unit effort (CPUE) was recorded 2.5-9.5 kg/day/ operation during the study periods. Mullets were the dominated group contributing 30% to the catch, followed by Otolithoides pama (15%), Lates calcarifer (14%), Macrobrachium rosenbergii (12%), catfishes (8%), Harpadon neherius (6%), Cynoglossus cynoglossus (4%), Eleutheronema tetradactylum (3%), juvenile Tenualosa ilisha (2%) and others (6%) during peak season (November-February). The mean profit per net per year was estimated to be 0.14 and 0.18 lakh for Bhadbhut and Mehgam centres, respectively. Due to less profit, high capital requirement, and operational cost, bag net fishery is gradually declining in the Narmada estuary. Bag net fishery was found to be destructive and needs to be replaced with alternative nets with higher mesh sizes for sustainable exploitation of the resources. Key words Bag net fishery; catch composition; profitability; sustainability; Narmada estuary